ADGRV1 Variants in Febrile Seizures/Epilepsy With Antecedent Febrile Seizures and Their Associations With Audio-Visual Abnormalities - Zhou, Peng; Meng, Heng; Liang, Xiaoyu; Lei, Xiaoyun; Zhang, Jingwen; Bian, Wenjun; He, Na; Lin, Zhijian; Song, Xingwang; Zhu, Weiwen; Hu, Bin; Li, Bingmei; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective ADGRV1 gene encodes adhesion G protein-coupled receptor-V1 that is involved in synaptic function. ADGRV1 mutations are associated with audio-visual disorders. Although previous experimental studies suggested that ADGRV1 variants were associated with epilepsy, clinical evidence is limited and the phenotype spectrum is to be defined. Methods Trio-based targeting sequencing was performed in a cohort of 101 cases with febrile seizure (FS) and epilepsy with antecedent FS. Protein modeling was used to assess the damaging effects of variants. The genotype-phenotype correlations of the ADGRV1 variants in epilepsy and audio-visual disorders were analyzed. Results ADGRV1 variants were identified in nine unrelated cases (8.91%), including two heterozygous frameshift variants, six heterozygous missense variants, and a pair of compound heterozygous variants. These variants presented a statistically higher frequency in this cohort than that in control populations. Most missense variants were located at CalX-β motifs and changed the hydrogen bonds. These variants were inherited from the asymptomatic parents, indicating an incomplete penetrance. We also identified SCN1A variants in 25 unrelated cases (24.75%) and SCN9A variants in 3 unrelated cases (2.97%) in this cohort. Contrary to SCN1A variant-associated epilepsy that revealed seizure was aggravated by sodium channel blockers, ADGRV1 variants were associated with mild epilepsy with favorable responses to antiepileptic drugs. The patients denied problems with audio-visual-vestibular abilities in daily life. However, audio-visual tests revealed auditory and visual impairment in the patient with compound heterozygous variants, auditory or vestibular impairment in the patients with heterozygous frameshift, or hydrogen-bond changed missense variants but no abnormalities in the patients with missense variants without hydrogen-bond changes. Previously reported ADGRV1 variants that were associated with audio-visual disorders were mostly biallelic/destructive variants, which were significantly more frequent in the severe phenotype of audio-visual disorders (Usher syndrome 2) than in other mild phenotypes. In contrast, the variants identified in epilepsy were monoallelic, missense mainly located at CalX-β, or affected isoforms VLGR1b/1c. Significance ADGRV1 is potentially associated with FS-related epilepsy as a susceptibility gene. The genotype, submolecular implication, isoforms, and damaging severity of the variants explained the phenotypical variations. ADGRV1 variant-associated FS/epilepsy presented favorable responses to antiepileptic drugs, implying a clinical significance.